Home kitchen ventilation, cooking fuels, and lung cancer risk in a prospective cohort of never smoking women in Shanghai, China. Issue 3 (28th June 2014) - Kim, Christopher; Gao, Yu‐Tang; Xiang, Yong‐Bing; Barone‐Adesi, Francesco; Zhang, Yawei; Hosgood, H. Dean; Ma, Shuangge; Shu, Xiao‐ou; Ji, Bu‐Tian; Chow, Wong‐Ho; Seow, Wei Jie; Bassig, Bryan; et al.
<x xml:space="preserve">Abstract</x> Indoor air pollution (IAP) caused by cooking has been associated with lung cancer risk in retrospective case–control studies in developing and rural countries. We report the association of cooking conditions, fuel use, oil use, and risk of lung cancer in a developed urban population in a prospective cohort of women in Shanghai. A total of 71, 320 never smoking women were followed from 1996 through 2009 and 429 incident lung cancer cases were identified. Questionnaires collected information on household living and cooking practices for the three most recent residences and utilization of cooking fuel and oil, and ventilation conditions. Cox proportional hazards regression estimated the association for kitchen ventilation conditions, cooking fuels, and use of cooking oils for the risk of lung cancer by hazard ratios (HR) with 95% confidence intervals (95% CI). Ever poor kitchen ventilation was associated with a 49% increase in lung cancer risk (HR: 1.49; 95% CI: 1.15–1.95) compared to never poor ventilation. Ever use of coal was not significantly associated. However, ever coal use with poor ventilation (HR: 1.69; 95% CI: 1.22–2.35) and 20 or more years of using coal with poor ventilation (HR: 2.03; 95% CI: 1.35–3.05) was significantly associated compared to no exposure to coal or poor ventilation. Cooking oil use was not significantly associated. These results demonstrate that IAP from poor ventilation of coal combustion increases the risk of lung cancer and is an important public health issue in cities across China where people may have lived in homes with inadequate kitchen ventilation.